"No die, no rest"? Coercive Discipline in Liberian Military Organisations. Issue 2 (August 2015) - Käihkö, Ilmari
Discipline forms the backbone of all military organisations. While discipline is traditionally associated with draconian punishment, this association is increasingly only applied to non-Western contexts. African rebel movements and similar, weak organisations are represented especially often as lacking non-coercive means of instilling discipline. This article explores the utility of coercive discipline in one such context – the Second Liberian Civil War (1999–2003). I argue that Liberia's weak military organisations faced significant restrictions when it came to employing direct coercion. Executions, which are often equated with coercion in existing literature, threatened to rive the already frail organisations. Even other formal instruments of discipline, such as military hierarchies and rules and regulations, remained contested throughout the war. Consequently, more indirect means were adopted. Ultimately, the main users of coercion were not military organisations, but peers. This suggests that it is easier for strong organisations to coerce their members, and that the relationship between coercion and organisational strength may need to be reassessed. Furthermore, existing positive perceptions of camaraderie between brothers-in-arms requires re-evaluation.